Actual Aspects of Quality Control and Standardization of Rosehip Fruits - D. A. Zhdanov; V. A. Kurkin; V. B. Braslavsky; A. I. Agapov (Разработка и регистрация лекарственных средств)
Introduction. Currently, herbal medicines are becoming increasingly popular. In this regard, of particular interest are medicinal herbal preparations based on rosehip fruits, which have a tonic, choleretic and wound healing effect due to the presence of ascorbic acid, flavonoids and carotenoids. According to the State Pharmacopoeia of the Russian Federation (SP RF) of the XIV edition, the determination of the main groups of biologically active substances (BAS) by thin-layer chromatography (TLC) is carried out only by the presence of ascorbic acid, while the sensitivity of the method does not allow it to be detected in rosehip fruits of low-vitamin species.Aim. Aim is the development of new approaches to control quality and standardization of Rosehip fruits with using of modern pharmacognostic analysis methods.Materials and methods. Prepared in Samara Region, the Republic of Mari El Rosehip fruits samples in 2020 and commercial samples from various manufacturers. TLC, UV/Vis-spectroscopy and high-performance liquid chromatography (HPLC) methods were used for determination the main BAS groups.Results and discussion. The introduction of flavonoids as one of the definitioned groups of BAS in rosehip fruits along with ascorbic acid was justified. A technique for the identification of ascorbic acid by UV/Vis-spectroscopy (wavelength 264 ± 2 nm) was developed and shown the determination possibility of this substance by HPLC.Conclusion. So phytochemical study results the expediency of the using of modern approaches to quality control and standardization of rosehip fruits, consisting in the qualitative determination of ascorbic acid by UV/Vis-spectroscopy and HPLC, as well as rutin by TLC, was justified.